2021
DOI: 10.1007/s00259-021-05502-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nodal staging between CT, MRI, and [18F]-FDG PET/MRI in patients with newly diagnosed breast cancer

Abstract: Purpose To compare CT, MRI, and [18F]-fluorodeoxyglucose positron emission tomography ([18F]-FDG PET/MRI) for nodal status, regarding quantity and location of metastatic locoregional lymph nodes in patients with newly diagnosed breast cancer. Materials and methods One hundred eighty-two patients (mean age 52.7 ± 11.9 years) were included in this prospective double-center study. Patients underwent dedicated contrast-enhanced chest/abdomen/pelvis computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 44 publications
(46 reference statements)
0
13
0
1
Order By: Relevance
“…In a more recent paper, a prospective comparison of nodal staging between CT, MRI, and 18 F‐FDG PET/MRI was performed in 182 breast cancer patients. The authors found that 18 F‐FDG PET/MRI outperformed CT and MRI in detecting axillary lymph node metastases at every level, revealing the presence of 193 lesions, whereas 123 and 104 lesions were detected by MRI and CT, respectively 56 . Recent evidence supporting the good performance of PET/MRI for the preoperative assessment of axillary lymph nodes has led to dedicated prospective clinical trials aiming to compare PET/MRI with axillary surgery or sentinel lymph node biopsy in early and advanced breast cancer 57 .…”
Section: Is There Value For Breast Pet/mri In Clinical Practice?mentioning
confidence: 99%
“…In a more recent paper, a prospective comparison of nodal staging between CT, MRI, and 18 F‐FDG PET/MRI was performed in 182 breast cancer patients. The authors found that 18 F‐FDG PET/MRI outperformed CT and MRI in detecting axillary lymph node metastases at every level, revealing the presence of 193 lesions, whereas 123 and 104 lesions were detected by MRI and CT, respectively 56 . Recent evidence supporting the good performance of PET/MRI for the preoperative assessment of axillary lymph nodes has led to dedicated prospective clinical trials aiming to compare PET/MRI with axillary surgery or sentinel lymph node biopsy in early and advanced breast cancer 57 .…”
Section: Is There Value For Breast Pet/mri In Clinical Practice?mentioning
confidence: 99%
“…However, the prospects of correlating metabolic functional imaging with functional and structural MRI parameters may be attractive not only for answering research questions but ultimately for translation to clinical imaging 207 . E.g., FDG-PET-MRI has been found to outperform MRI in evaluating tumor size and nodal metastases in rectal cancer 208 , and MRI and CT for nodal staging in breast cancer 209 .…”
Section: Hybrid Imaging: Positron-emission Tomography Ct and Mrimentioning
confidence: 99%
“…Currently, the diagnosis of molecular subtypes of breast tumor is mainly based on surgical or puncture biopsy immunohistochemistry, which is the gold standard for the detection of ER, PR, HER-2, and Ki-67 expression, and the reliability of its tests also depends on the handling of the tissue, which may sometimes lead to false positives and false negatives [ 15 ]. Therefore, predicting the molecular subtype of breast tumor by imaging signs can further improve the reliability of preoperative treatment strategies, which is of great value for the precise treatment of breast tumor and improving the prognosis.…”
Section: Related Workmentioning
confidence: 99%